Lithium ion battery and electric device
By using structural glue with moderate shear force and thermal management components in fast-charging lithium-ion batteries, combined with electrolyte with high ionic conductivity, the problem of structural glue failure of the battery at high temperatures is solved, and the structural stability and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202510005306.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
AI Technical Summary
The structural glue of the fast-charging lithium-ion battery fails at high temperatures, causing the battery cell to fall off, affecting the normal use and safety performance of the battery.
Structural glue with shear force in the range of 5Mpa to 15Mpa, and thermal management components are provided on the surface with the largest area of the battery cell to reduce temperature rise. At the same time, electrolyte with high ionic conductivity and structural glue with appropriate thermal conductivity and dynamic viscosity are selected.
It improves the structural stability and safety performance of lithium-ion batteries at high temperatures, reduces the risk of structural glue failure, and extends the battery's service life.
Smart Images

Figure CN119833862A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to a lithium-ion battery and an electrical device. Background Art
[0002] In recent years, secondary batteries, mainly lithium-ion batteries, have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, and have thus achieved great development.
[0003] As people continue to pursue efficiency in life, fast-charging lithium-ion batteries have become a focus of development. During the charging process, the temperature of the battery cells of lithium-ion batteries rises as the electrochemical reaction occurs. The temperature rise of the battery cells of fast-charging lithium-ion batteries is more prominent. Excessive temperature of fast-charging lithium-ion batteries will cause the structural adhesive in the lithium-ion batteries to fail, affecting the normal use of fast-charging lithium-ion batteries. Therefore, how to improve the structural stability of fast-charging lithium-ion batteries is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application is made in view of the above-mentioned technical problems, and its purpose is to provide a lithium ion battery and an electrical device, wherein the lithium ion battery has excellent structural stability at high temperatures.
[0005] In a first aspect, a lithium-ion battery is provided, wherein the time t for charging the lithium-ion battery from 10% SOC to 80% SOC satisfies: t≤15min; the lithium-ion battery comprises: a housing and a battery cell arranged in the housing, the battery cell being bonded to the housing by a structural adhesive; and the shear force F of the structural adhesive at 50°C-70°C satisfies: 5Mpa≤F≤15Mpa.
[0006] In the embodiments of the present application, the lithium-ion battery is a lithium-ion battery with fast charging capability. By selecting a structural adhesive in the lithium-ion battery whose shear force meets the above conditions, the lithium-ion battery can have good structural stability even at higher temperatures, thereby improving the problem of the structural adhesive failing at high temperatures and causing the battery cell to fall off, thereby improving the structural stability and safety performance of the lithium-ion battery.
[0007] In a possible implementation, the battery cell includes an electrolyte, and the ion conductivity σ of the electrolyte satisfies: 9mS / cm≤σ≤25mS / cm.
[0008] In the embodiments of the present application, by selecting an electrolyte with higher ionic conductivity, the internal impedance of the battery cell can be reduced, thereby reducing the temperature rise of the lithium-ion battery during fast charging, and helping to reduce the risk of failure of the structural adhesive in the lithium-ion battery under high temperature conditions.
[0009] In a possible implementation, the structural adhesive includes at least one of polyurethane structural adhesive, acrylic structural adhesive, silicone, and epoxy structural adhesive.
[0010] In a possible implementation, the thermal conductivity k of the structural adhesive satisfies: 0.05W / (m×K)≤k≤1.2W / (m×K); optionally, 0.2W / (m×K)≤k≤0.8W / (m×K).
[0011] In the embodiments of the present application, by selecting a structural adhesive with a smaller thermal conductivity, the heat transfer from the battery cell to the structural adhesive can be reduced, thereby reducing the risk of failure of the structural adhesive under high temperature conditions.
[0012] In a possible implementation, the dynamic viscosity η of the structural adhesive satisfies: 200cps≤η≤100000cps.
[0013] In a possible implementation, the polyurethane structural adhesive includes an inorganic filler, and the mass fraction M1 of the inorganic filler satisfies the following condition: 5wt%≤M1≤80wt%, based on the total mass of the polyurethane structural adhesive.
[0014] In a possible implementation, 10 wt % ≤ M1 ≤ 50 wt %.
[0015] In the embodiments of the present application, controlling the mass fraction of the inorganic filler within the above range helps to reduce the thermal conductivity of the structural adhesive.
[0016] In a possible implementation, raw materials for preparing the polyurethane structural adhesive include polyamide and polyol, and a volume ratio v1:v2 of the polyamide to the polyol satisfies: 4:1≤v1:v2≤1:4.
[0017] In the embodiments of the present application, by controlling the volume ratio of polyamide to polyol within the above range, it is helpful to make the structural adhesive still have a larger dynamic viscosity at a higher temperature.
[0018] In a possible implementation, the lithium-ion battery includes a thermal management component, the thermal management component is attached to the surface of the battery cell with the largest area, and the thermal management component includes a flow channel, and the flow channel is used to accommodate a fluid to adjust the temperature of the battery cell.
[0019] In the embodiments of the present application, by arranging a thermal management component on the surface of the battery cell with the largest area, the temperature rise of the battery cell during fast charging can be reduced, thereby reducing the temperature of the lithium-ion battery during fast charging, improving the problem of battery cell falling off due to failure of structural adhesive at high temperature, and improving the structural stability and safety performance of the lithium-ion battery.
[0020] In a possible implementation, the electrolyte includes a carboxylate solvent, and the carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate and ethyl acrylate.
[0021] In the embodiments of the present application, the selection of carboxylic acid ester solvents helps to improve the ionic conductivity of the electrolyte, thereby reducing the temperature rise of the battery cells during fast charging and helping to reduce the risk of failure of the structural adhesive under high temperature conditions.
[0022] In a possible implementation, based on the total mass of the electrolyte, the mass fraction W1 of the carboxylic acid ester solvent satisfies: 5wt%≤W1≤80wt%.
[0023] In a possible implementation, 10 wt % ≤ W1 ≤ 40 wt %.
[0024] In a possible implementation, the lithium-ion battery includes a positive electrode active material, the positive electrode active material includes a lithium-containing transition metal oxide, and the lithium transition metal oxide includes Li 1+a [Ni x Co y Mn z M b ]O 2-c ; wherein M includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 0.7≥x≥0.65, 0.12≥y≥0.07, 0.3>z>0, 0.3>b≥0, 0.5≥c≥0.
[0025] In a possible implementation, the electrolyte includes a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
[0026] In a possible implementation, the electrolyte includes an electrolyte salt, and the electrolyte salt includes at least one of LiFSI.
[0027] In a second aspect, an electrical device is provided, wherein the electrical device comprises the lithium-ion battery in any embodiment of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0029] Figure 1 An exploded diagram of a lithium-ion battery.
[0030] Figure 2 A schematic structural diagram of a battery cell.
[0031] Figure 3 An exploded diagram of a battery cell.
[0032] Figure 4 An exploded diagram of a thermal management component. DETAILED DESCRIPTION
[0033] Hereinafter, the embodiments of the lithium-ion battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0034] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] In the description of this application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating directions or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting this application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0036] If not otherwise specified, in this application, the phrase "A and / or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A and / or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0037] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0038] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] If not specifically stated otherwise, any undefined terms have their art-recognized meanings.
[0040] Next, embodiments of the present application are introduced.
[0041] In recent years, secondary batteries have been widely used in power tools, electronic products, electric vehicles, aerospace and other fields due to their high energy density and long service life, and have achieved great development. Usually, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. Among them, the electrolyte plays a role in conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which allows active ions to pass through while preventing the positive and negative electrodes from short-circuiting, so that the electrochemical reaction of the secondary battery proceeds normally.
[0042] Take lithium-ion batteries as an example. Lithium-ion batteries are a typical secondary battery. Because they rely on the chemical reaction of lithium ions intercalating and disintercalating between the positive and negative electrodes for charging and discharging, lithium-ion batteries are also called rocking-chair batteries. During the charging process of lithium-ion batteries, lithium ions are released from the positive electrode active material, move to the negative electrode through the conduction of the electrolyte and embed into the negative electrode active material; and during the discharge process, lithium ions are released from the negative electrode active material, move to the positive electrode through the conduction of the electrolyte and embed into the positive electrode active material.
[0043] It should be understood that the "lithium insertion" and "embedding" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "extraction", "delithium" and "extraction" processes described in this application refer to the process in which lithium ions are extracted from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.
[0044] As the application scope of lithium-ion batteries becomes wider and wider, and the usage scenarios become more and more diverse, new requirements are put forward for the charging capacity of lithium-ion batteries. For example, for power vehicles, mileage anxiety and long charging time have become the main problems hindering their development. Therefore, the fast charging (FC) capability is called an important goal for the development of lithium-ion batteries. Fast charging is referred to as fast charging, which refers to charging the battery to a full or nearly full state through high-power direct current in a short period of time. The industry in different regions has different standards for the specific definition of fast charging. Generally speaking, if the battery can be charged to 80% of its full power in 30min to 60min, it is considered to be fast charging, and the charging time within 20min can be considered to be super fast charging; further, further, the charging time is less than 15min can be considered to be in the range of extreme fast charging (XFC). In the embodiment of the present application, a fast-charging lithium-ion battery refers to a lithium-ion battery with fast charging capability.
[0045] During the charging process of lithium-ion batteries, the temperature of lithium-ion batteries rises as electrochemical reactions occur, that is, there is a temperature rise in the lithium-ion battery during the charging process. The greater the charging current, the higher the temperature rise during the charging process. Therefore, for fast-charging lithium-ion batteries, the temperature of the battery cells is higher during the fast-charging process. Generally speaking, the battery cells in lithium-ion batteries are bonded to the lithium-ion battery case through structural adhesives, which play the role of connecting the battery cells to the case and fixing the battery cells. In fast-charging lithium-ion batteries, due to the high temperature of the battery cells during the fast-charging process, the structural adhesive is easily failed, causing the internal structure of the lithium-ion battery to be unstable, affecting the normal use of the lithium-ion battery. For example, during the driving of a car, once the battery cell is debonded, it may cause the battery cell to move in the case, or collide with other battery cells or the case during the bumpy ride of the car, causing safety problems in serious cases.
[0046] In view of this, an embodiment of the present application provides a lithium-ion battery and an electrical device, wherein the lithium-ion battery has good structural stability during fast charging.
[0047] Next, the lithium-ion battery provided by the present application is introduced.
[0048] [Lithium-ion battery]
[0049] First, a lithium-ion battery is provided, wherein the time t for charging the lithium-ion battery from 10% SOC to 80% SOC satisfies: t≤15min; the lithium-ion battery comprises: a box body and a battery cell arranged in the box body, the battery cell is bonded to the box body by a structural adhesive; the shear force F of the structural adhesive at 50°C-70°C satisfies: 5Mpa≤F≤15Mpa.
[0050] Figure 1 Figure 1 is a schematic exploded diagram of a lithium-ion battery. Figure 1 As shown, the lithium-ion battery 10 may be a single physical module including a plurality of battery cells 20 connected in series, in parallel or in mixed series to provide a higher voltage and capacity. The lithium-ion battery 10 may also include a housing 3 in which the battery cells 20 are accommodated.
[0051] The box body 3 has a hollow structure inside, and multiple battery cells 20 are connected in parallel, in series, or in a mixed combination and placed inside the box body 3. The box body 3 may include a first box body portion 31 and a second box body portion 32, which cover each other to form the box body 3. The shapes of the first box body portion 31 and the second box body portion 32 may be determined according to the shapes of the components contained inside, for example, according to the shapes of the combination of multiple battery cells 20 contained inside, and at least one of the first box body portion 31 and the second box body portion 32 may have an opening. Figure 1As shown, the first box body 31 and the second box body 32 can both be hollow cuboids and each have an open face, the opening of the first box body 31 and the opening of the second box body 32 are arranged opposite to each other, and the first box body 31 and the second box body 32 are buckled together to form a box body 3 with a closed chamber, which can be used to accommodate multiple battery cells 20. Multiple battery cells 20 are connected in parallel, in series, or in mixed combination and placed in the box body 3 formed by the buckling of the first box body 31 and the second box body 32.
[0052] For example, Figure 1 Different from the above, only one of the first box body 31 and the second box body 32 may be a hollow cuboid with an opening, while the other may be a plate-shaped to cover the opening. For example, if the second box body 32 is a hollow cuboid with an opening, and the first box body 31 is a plate-shaped, the first box body 31 covers the opening of the second box body 32 to form a box body 3 with a closed chamber, which can be used to accommodate multiple battery cells 20.
[0053] Structural adhesive is an important component that achieves tight bonding between battery cells 20 and between battery cells 20 and box body 3, so that lithium-ion battery 10 has an integrated structure. In addition to meeting the need to fix the internal structure of lithium-ion battery 10, structural adhesive can also protect battery cells 20 and maintain the stability of the structure of lithium-ion battery 10 when lithium-ion battery 10 is in vibration, fall, etc. At present, the improvement of structural adhesive is mainly focused on improving the thermal conductivity of structural adhesive.
[0054] The lithium-ion battery 10 has a fast charging capability of being charged from 10% SOC to 80% SOC in less than or equal to 15 minutes. At this time, each battery cell 20 in the lithium-ion battery 10 also has a fast charging capability of being charged from 10% SOC to 80% SOC in less than or equal to 15 minutes.
[0055] The fast charging process can be a constant current charging process or a step charging process. The constant current charging process is to charge the battery cell 20 at a fixed charging rate. The charging rate represents the ratio of the charging current to the capacity of the battery cell 20. For example, for a battery that supports 4C charging, the charging current can reach four times the battery capacity. The charging rate can be calculated by the ratio of the charging current and the capacity of the battery cell 20. During the fast charging process of the battery cell 20, the charging rate can also be variable. For example, when the battery cell 20 is charged at a charging rate greater than or equal to 2.8C, the charging time from 10% SOC to 80% SOC is less than or equal to 15min. The current density is the equivalent charging rate of the battery cell 20 during the process of charging from 10% SOC to 80% SOC. In other words, in the process of charging from 10% SOC to 80% SOC, the charging rate may gradually decrease from greater than 2.8C to less than 2.8C. During this process, the battery cell 20 may undergo a transition from constant current charging to constant voltage charging, so the charging rate is not constant. For example, the battery cell 20 starts charging at a room temperature of 25°C, charging from 10% SOC to 80% SOC, and the charging time is 10 minutes (equivalent charging rate ≥ 4C). The charging process can be: initially charging from 10% SOC to 45% SOC at 5C, then charging from 45% SOC to 50% SOC at 4.6C, charging from 50% SOC to 55% SOC at 4.3C, and charging from 3.9C to 4.6C.
[0056] 55% SOC to 60% SOC, 3.6C from 60% SOC to 65% SOC, 3.3C from
[0057] 65% SOC is charged to 70% SOC, 3.1C is charged from 70% SOC to 75% SOC, 2.9C is charged from 75% SOC to 80% SOC, and charging is completed. The charging time of the battery cell 20 from 0% SOC to 100% SOC at 1C is 60min. Therefore, when the charging time of the battery cell 20 from 10% SOC to 80% SOC is measured to be 10min, the equivalent charging rate of the process can be calculated as: [(80% SOC-10% SOC) / (100% SOC-0% SOC)]×[(1C×60min) / 10min]=4.2C.
[0058] If the battery cell 20 is placed on a charging pile for charging, the time it takes to charge from 0% SOC to 100% SOC can also be directly recorded. For example, if the time is about 15 minutes (the error does not exceed 1 minute), it is generally considered to be a 4C fast-charging battery. For another example, if the time is about 12 minutes (the error does not exceed 1 minute), it is generally considered to be a 5C fast-charging battery. For another example, if the time is about 10 minutes (the error does not exceed 1 minute), it is generally considered to be a 6C fast-charging battery.
[0059] For fast-charged lithium-ion batteries 10, the temperature rise of the lithium-ion batteries 10 during the charging process is much greater than that of ordinary lithium-ion batteries 10, resulting in a higher temperature of the lithium-ion batteries 10 during or after the charging process. The structural adhesive used in ordinary lithium-ion batteries 10 is prone to failure in fast-charged lithium-ion batteries 10.
[0060] In this embodiment, F can be 5Mpa, 6Mpa, 7Mpa, 8Mpa, 9Mpa, 10Mpa, 11Mpa, 12Mpa, 13Mpa, 14Mpa, 15Mpa, or its value is within the range obtained by combining any two of the above values. The structural adhesive has a shear force of 5Mpa-15 Mpa at 50℃-70℃, which means that the structural adhesive can still meet the bonding requirements between the battery cell 20 and the box 3 when the temperature of the lithium-ion battery 10 is high. Therefore, by matching the fast-charging lithium-ion battery 10 with a structural adhesive whose shear strength meets the above requirements at high temperatures, the risk of debonding of the battery cell 20 can be reduced during the charging process of the fast-charging lithium-ion battery 10, thereby improving the structural stability of the fast-charging lithium-ion battery 10 and helping to improve the safety performance of the fast-charging lithium-ion battery 10.
[0061] In one embodiment, the battery cell 20 includes an electrolyte, and the ion conductivity σ of the electrolyte satisfies: 9 mS / cm≤σ≤25 mS / cm.
[0062] Specifically, σ can be 9mS / cm, 10mS / cm, 11mS / cm, 12mS / cm, 13mS / cm, 14mS / cm, 15mS / cm, 16mS / cm, 17mS / cm, 18mS / cm, 19mS / cm, 20mS / cm, 21mS / cm, 22mS / cm, 23mS / cm, 24mS / cm, 25mS / cm, or a value within the range obtained by combining any two of the above values. It should be understood that, unless otherwise specified, the ionic conductivity referred to in this application refers to the ionic conductivity of the electrolyte at 20°C to 30°C.
[0063] Figure 2 This is a schematic structural diagram of a battery cell of the present application. Figure 3This is a schematic exploded view of a battery cell of the present application.
[0064] like Figure 2-3 As shown, the battery cell 20 generally includes a shell 201 and an electrode assembly 202 disposed in the shell 201. The shell 201 is a component for encapsulating the electrode assembly 202 and the electrolyte. The material of the shell 201 can be a steel shell, an aluminum shell, a plastic shell (such as polypropylene), a composite metal shell (such as a copper-aluminum composite shell) or an aluminum-plastic film, etc. The shell 201 can include a plurality of walls, so that the battery cell 20 is a polyhedral structure. Specifically, the shell 201 includes a shell 2012 and an end cover 2011. Exemplarily, the shell 201 can be a cuboid or a substantially cuboid, and the shell 20 can include six walls, each of which is rectangular or substantially rectangular. Correspondingly, the shell 2012 can also be a polyhedral structure with an opening.
[0065] The shell 2012 can be in various shapes, such as a cylinder, a cuboid, etc. The shape of the shell 2012 can be determined according to the specific shape of the electrode assembly 202. For example, if the electrode assembly 202 is a cylindrical structure, the shell 2012 can be a cylindrical structure; if the electrode assembly 202 is a cuboid structure, the shell 2012 can be a cuboid structure. Of course, the end cap 2011 can also be a variety of structures, such as the end cap 2011 being a plate-like structure or a hollow structure with one end open. It should be understood that the shell 201 is not limited to the aforementioned structure, and the shell 201 can also be other structures, for example, the shell 201 includes a shell 2012 and two end caps 2011, the shell 2012 is a hollow structure with two opposite openings, and one end cap 2011 is correspondingly covered at an opening of the shell 2012 and forms a sealed connection to form a sealed space for accommodating the electrode assembly 202 and the electrolyte.
[0066] In the present embodiment, by selecting an electrolyte with an ion conductivity within the above range, on the one hand, the electrolyte with high ion conductivity helps to improve the fast charging performance of the battery cell 20; on the other hand, it can reduce the internal impedance of the battery cell 20, thereby reducing the temperature rise of the battery cell 20 during the fast charging process, and reducing the temperature of the lithium-ion battery 10 during or after the fast charging process. Thus, the problem of the battery cell 20 falling off due to the failure of the structural adhesive at high temperature is improved, thereby improving the structural stability and safety performance of the lithium-ion battery 10.
[0067] In one embodiment, the structural adhesive includes at least one of polyurethane structural adhesive, acrylic structural adhesive, silicone, and epoxy structural adhesive.
[0068] In one embodiment, the thermal conductivity k of the structural adhesive satisfies: 0.05W / (m×K)≤k≤1.2W / (m×K); optionally, 0.2W / (m×K)≤k≤0.8W / (m×K).
[0069] Specifically, k can be 0.05W / (m×K), 0.1W / (m×K), 0.2W / (m×K), 0.3W / (m×K), 0.4W / (m×K), 0.5W / (m×K), 0.6W / (m×K), 0.7W / (m×K), 0.8W / (m×K), 0.9W / (m×K), 1.0W / (m×K), 1.1W / (m×K), 1.2W / (m×K), or its value is within the range obtained by combining any two of the above values.
[0070] At present, the improvement of structural adhesive requires that the structural adhesive has a higher thermal conductivity to help the lithium-ion battery 10 dissipate heat, but ignores the problem that the structural adhesive of the fast-charged lithium-ion battery 10 is easy to fail at high temperatures. This embodiment takes the opposite approach. By matching the fast-charged lithium-ion battery 10 with a structural adhesive with a low thermal conductivity, it is possible to reduce the heat transfer from the battery cell 20 to the structural adhesive, and reduce the impact of the heating of the battery cell 20 on the structural adhesive, thereby improving the problem of the failure of the structural adhesive at high temperatures and causing the battery cell 20 to fall off, and improving the structural stability and safety performance of the lithium-ion battery 10.
[0071] In one embodiment, the dynamic viscosity η of the structural adhesive satisfies: 200cps≤η≤100000cps.
[0072] Specifically, η can be 200cps, 400cps, 600cps, 800cps, 1000cps, 2000cps, 4000cps, 6000cps, 8000cps, 10000cps, 20000cps, 40000cps, 60000cps, 80000cps, 100000cps, or a value thereof within the range obtained by combining any two of the above values. The structural adhesive of the present application still has a dynamic viscosity of 200cps-100000cps at 50°C-70°C, thereby improving the structural stability and safety performance of the lithium-ion battery 10.
[0073] In one embodiment, the polyurethane structural adhesive includes inorganic fillers. Based on the total mass of the polyurethane structural adhesive, the mass fraction M1 of the inorganic filler satisfies: 5wt%≤M1≤80wt%; optionally, 10wt%≤M1≤50wt%.
[0074] Specifically, M1 can be 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, or its value is within the range obtained by combining any two of the above values. When M1 is 10wt%-50wt%, by controlling the mass fraction of the inorganic filler in the polyurethane structural adhesive within a smaller range, it is helpful to reduce the thermal conductivity of the polyurethane structural adhesive.
[0075] The inorganic filler can be a silicate inorganic filler such as mica powder, talcum powder, etc., or a carbonate inorganic filler such as calcium carbonate, magnesium carbonate, etc., or a sulfate inorganic filler such as barium sulfate, lithopone, etc. The proportion of inorganic fillers in the structural adhesive has a certain influence on the thermal conductivity of the structural adhesive. Generally speaking, the larger the proportion of inorganic fillers, the higher the thermal conductivity and the better the thermal conductivity. Based on this, this embodiment selects a polyurethane structural adhesive with a relatively small proportion of inorganic fillers, so that the thermal conductivity of the structural adhesive meets the design requirements, thereby reducing the thermal conductivity of the structural adhesive and reducing the risk of failure of the structural adhesive in the fast-charging lithium-ion battery 10.
[0076] In one embodiment, the raw materials for preparing the polyurethane structural adhesive include polyamide and polyol, and the volume ratio v1:v2 of the polyamide and the polyol satisfies: 4:1≤v1:v2≤1:4.
[0077] Specifically, v1:v2 can be 4:1, 3:2, 2.5:2.5, 2:3, 1:4, or any value thereof is within the range obtained by combining any two of the above values. In the process of preparing the polyurethane structural adhesive, by controlling the ratio of polyamide and polyol within the above range, the viscosity of the polyurethane structural adhesive at high temperature can be increased, so that the structural adhesive still has a shear force of 5Mpa-15Mpa at 50°C-70°C.
[0078] Polyol refers to an alcohol compound containing two or more hydroxyl groups in the molecule. For example, polyether polyols and polyester polyols. By controlling the ratio of polyamide and polyol, the ratio of long-chain polymers to short-chain polymers in polyurethane structural adhesives can be adjusted, thereby regulating the physical and chemical properties of polyurethane structural adhesives.
[0079] In one embodiment, the lithium-ion battery includes a thermal management component, which is attached to the largest surface of the battery cell 20 . The thermal management component includes a flow channel, which is used to contain a fluid to adjust the temperature of the battery cell 20 .
[0080] Figure 4 This is a schematic structural diagram of a thermal management component of the present application.
[0081] like Figure 4As shown, the heat management component 40 may include a first heat conducting plate 401 and a second heat conducting plate 402, and the flow channel 41 may be formed by providing a groove on the first heat conducting plate 401 and / or the second heat conducting plate 402. Taking the provision of a groove on the second heat conducting plate 402 as an example, the second heat conducting plate 402 is provided with a groove whose opening faces the first heat conducting plate 401. When the first heat conducting plate 401 and the second heat conducting plate 402 are provided in close contact, the first heat conducting plate 401 covers the opening of the groove, thereby forming a heat conducting plate 401 as shown in FIG. Figure 4 The hollow structure shown is the flow channel 41 .
[0082] It should be understood that although Figure 4 Although not shown in the figure, the flow channel 41 has an inlet and an outlet, and the fluid flows into the thermal management component 40 from the inlet and is discharged from the thermal management component 40 from the outlet after passing through the flow channel 41. The inlet and the outlet may be part of the flow channel 41 or may be independent components connected to the flow channel 41. The flow channels 41 may be independent or connected to each other. Figure 4 The shapes of the flow channels 41 shown are all strip-shaped, but the embodiments of the present application are not limited thereto.
[0083] For ease of processing, the thermal management component 40 is usually attached to the bottom wall surface of the battery cell 20. In this embodiment, the thermal management component 40 is attached to the surface of the battery cell 20 with the largest area, which can increase the heat exchange area between the battery cell 20 and the thermal management component 40, thereby reducing the temperature rise of the battery cell 20 during fast charging. In this way, the risk of structural adhesive failure in the fast-charging lithium-ion battery 10 is reduced, and the structural stability of the lithium-ion battery 10 is improved.
[0084] refer to Figure 2 , for example, the thermal management component can be attached to the surface a and the surface a of the battery cell 20. It should be understood that the thermal management component 40 is attached to the surface with the largest area of the battery cell 20, and the first heat conductive plate 401 can be attached to the battery cell 20, or the second heat conductive plate 402 can be attached to the battery cell 20. "Attachment" can be that the thermal management component 40 is directly attached to the surface of the battery cell 20, or it can be attached through an adhesive such as a thermal conductive glue to achieve heat exchange between the thermal management component 40 and the battery cell 20.
[0085] In one embodiment, the electrolyte includes a carboxylate solvent, and the carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate, and ethyl acrylate.
[0086] Specifically, carboxylate solvents have lower density and viscosity and higher ionic conductivity. In this embodiment, by selecting carboxylate solvents as at least part of the electrolyte solvent, the ionic conductivity of the electrolyte can be improved, which helps to improve the fast charging performance of the battery cell 20 and the lithium-ion battery 10. In addition, the electrolyte with high ionic conductivity can also reduce the DCR of the battery cell 20, help reduce the temperature rise of the battery cell 20 and the lithium-ion battery 10 during the fast charging process, and help reduce the risk of structural adhesive failure in the fast-charged lithium-ion battery 10.
[0087] In one embodiment, based on the total mass of the electrolyte, the mass content W1 of the carboxylate solvent satisfies: 5wt%≤W1≤80wt%; optionally, 10wt%≤W1≤40wt%.
[0088] Specifically, W1 can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, or its value is within the range obtained by combining any two of the above values. Carboxylic acid ester solvents are prone to side reactions and gas production at high temperatures. This embodiment can reduce the gas production of carboxylic acid ester solvents by controlling the mass content of the carboxylic acid ester solvents within a suitable range.
[0089] In one embodiment, the battery cell 20 includes a positive electrode active material including a lithium transition metal oxide.
[0090] Specifically, the positive electrode film layer of the positive electrode sheet contains positive electrode active materials. Lithium transition metal oxides refer to a class of oxides that include lithium and transition metal elements. Structurally, they include ternary materials with layered structures, LiCoO 2 、LiNiO 2 etc., including LiMn with spinel structure 2 O 4 Etc. Ternary materials refer to lithium transition metal oxides including three different transition metal elements. It should be understood that trace amounts of other transition metal elements may also be doped in ternary materials, and ternary materials doped with other transition metal elements are generally considered to still belong to ternary materials. In this embodiment, lithium transition metal oxides generally have a higher gram capacity, and selecting lithium transition metal oxides as at least part of the positive electrode active material helps to improve the energy density of the battery cell 20 and the lithium-ion battery 10.
[0091] In one embodiment, the lithium transition metal oxide includes a ternary material, and the ternary material satisfies the general formula: Li 1+a [Ni x Coy Mn z M b ]O 2-c ; wherein M includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 0.7≥x≥0.65, 0.12≥y≥0.07, 0.3>z>0, 0.3>b≥0, 0.5≥c≥0.
[0092] In one embodiment, the electrolyte includes a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
[0093] Specifically, carbonate solvents have lower viscosity, higher dielectric constant and good electrochemical stability. Lower viscosity is conducive to the rapid migration of lithium ions in the electrolyte, improving the fast charging performance of the battery cell 20 and the lithium-ion battery 10; higher dielectric constant is conducive to improving the solubility of lithium salt in the electrolyte, thereby helping to increase the concentration of lithium salt in the electrolyte; good electrochemical stability helps to increase the operating voltage range of the battery cell 20 and the lithium-ion battery 10, thereby increasing the capacity of the battery cell 20 and the lithium-ion battery 10. Therefore, this embodiment helps to improve the fast charging performance and cycle performance of high-capacity battery cells 20 and lithium-ion batteries 10 by using carbonate solvents as the solvent of the electrolyte on the basis of carboxylate solvents.
[0094] In one embodiment, the electrolyte includes an electrolyte salt including at least one of LiFSI.
[0095] Specifically, LiFSI is lithium bis(fluorosulfonyl)imide, which has a higher solubility in carboxylate solvents and is more soluble than LiPF 6 It has a higher lithium ion transfer number and good stability at high temperatures. Therefore, by selecting LiFSI as the electrolyte salt, it will not decompose and produce gas at high temperatures, which helps to further improve the fast charging cycle performance of the lithium ion battery 10.
[0096] Next, the negative electrode sheet, the positive electrode sheet and the separator in the battery cell 20 are introduced in more detail.
[0097] [Negative electrode]
[0098] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material.
[0099] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0100] In one embodiment, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0101] In one embodiment, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0102] In one embodiment, the negative electrode active material is a silicon-containing material. The silicon-containing material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, silicon-containing alloys, or silicon-oxygen-carbon composite materials. By selecting a silicon-containing material as the negative electrode active material, it is beneficial to further improve the volume energy density of the battery cell 20. Combined with the structural design of the battery cell 20 in the aforementioned embodiment, the battery cell 20 can have both high energy density and excellent safety performance.
[0103] In one embodiment, the negative electrode film layer further includes a binder. The binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0104] In one embodiment, the negative electrode film layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0105] In one embodiment, the negative electrode film layer further includes other additives, such as a thickener (eg sodium carboxymethyl cellulose (CMC-Na)).
[0106] In one embodiment, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet are formed into a negative electrode slurry. For example, the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a negative electrode slurry. Then, the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0107] [Positive electrode]
[0108] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0110] In one embodiment, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0111] In another embodiment, the positive electrode active material may also be a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may also include at least one of the following materials: an olivine-structured lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O 2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The battery will be accompanied by the deintercalation and consumption of Li during the charging and discharging process, and the molar content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is applied to the battery system, and the molar content of Li will change after the charge and discharge cycle. In the enumeration of positive electrode active materials in this application, the molar content of O is only an ideal state value. Lattice oxygen release will cause the molar content of O to change, and the actual molar content of O will fluctuate.
[0112] In one embodiment, the positive electrode film layer further includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0113] In one embodiment, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0114] In one embodiment, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet are respectively formed into positive electrode slurries. For example, the first positive electrode active material and / or the second positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry. Then, the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0115] [Electrolyte]
[0116] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0117] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0118] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0119] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0120] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0121] [Isolation film]
[0122] The present application has no particular limitation on the type of isolation membrane. For example, any known porous isolation membrane with good chemical stability and mechanical stability may be selected.
[0123] In one embodiment, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation. When the isolation membrane is a multi-layer composite film, the isolation membrane of the present application does not contain a PVDF coating.
[0124] In one embodiment, the negative electrode sheet, the positive electrode sheet and the separator may be formed into the electrode assembly 202 by a winding process or a lamination process.
[0125] The present application has no particular limitation on the shape of the battery cell 20 , which may be cylindrical, square, or any other shape.
[0126] In some embodiments, the lithium-ion battery 10 may further include other components. For example, the lithium-ion battery 10 may further include a busbar component, which may be used to achieve electrical connection between multiple battery cells 20, such as parallel connection, series connection, or mixed connection. Specifically, the busbar component may achieve electrical connection between the battery cells 20 by connecting the electrode terminals of the battery cells 20; or, the busbar component may also achieve electrical connection between the battery cells 20 by connecting other components of the battery cells 20. The busbar component may be fixed to the corresponding component of the battery cell 20 by welding, for example, it may be fixed to the electrode terminal, the sealing structure, or the housing by welding, etc., and the embodiments of the present application are not limited thereto.
[0127] The battery cells 20 can directly form the lithium-ion battery 10 , or they can first form a battery module, and then multiple battery modules form the lithium-ion battery 10 .
[0128] [Electrical devices]
[0129] An embodiment of the present application provides an electrical device, comprising the lithium-ion battery described in the above embodiment.
[0130] The electrical device may be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, an electric tool, and the like. The vehicle may be a fuel vehicle, a gas vehicle, or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, and the like; the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, and the like; the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, and the like; the electric tool may include a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, and the like. The embodiments of the present application do not impose any special restrictions on the above-mentioned electrical devices.
[0131] The present application provides an electrical device, which is a vehicle.
[0132] The vehicle can be a fuel vehicle, a gas vehicle or a new energy vehicle. The new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor, a controller and a lithium-ion battery 10 can be arranged inside the vehicle, and the controller is used to control the lithium-ion battery 10 to power the motor. For example, a lithium-ion battery 10 can be arranged at the bottom, front or rear of the vehicle. The lithium-ion battery 10 can be used to power the vehicle. For example, the lithium-ion battery 10 can be used as an operating power source for the vehicle, for the circuit system of the vehicle, for example, for the working power requirements during the start-up, navigation and operation of the vehicle. In another embodiment of the present application, the lithium-ion battery 10 can not only be used as an operating power source for the vehicle, but also as a driving power source for the vehicle, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle.
[0133] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0134] [Examples and Comparative Examples]
[0135] Example 1
[0136] (1) Preparation of negative electrode sheet
[0137] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in deionized water at a mass ratio of 96:1.5:1.5:1.0, and the mixture is fully stirred and mixed to prepare a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet.
[0138] (2) Preparation of positive electrode sheet
[0139] The positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive agent (acetylene black) are mixed evenly in a mass ratio of 97.5:1.5:1, dissolved in a solvent N-methylpyrrolidone (NMP), and fully stirred and mixed to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0140] (3) Preparation of battery cells
[0141] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly 202; the electrode assembly 202 is placed in a housing 2012, and an electrolyte is added. After packaging, standing, forming, aging, and other processes, a battery cell 20 is obtained. The ionic conductivity of the electrolyte is σ=12.8 mS / cm.
[0142] (4) Preparation of lithium-ion batteries
[0143] The battery cell 20 is attached to the box body 3 by polyurethane structural adhesive, and the thermal management component 40 is attached to the side wall of the battery cell 20 with the largest area. Figure 1 The two columns of battery cells 20 are connected in series via a busbar component, and the four battery cells 20 in each column are connected in parallel to form a lithium-ion battery 10 .
[0144] In the lithium-ion battery of Example 1, the shear force F of the polyurethane structural adhesive at 50° C.-70° C. is 9 MPa, and the thermal conductivity k of the structural adhesive is 0.3 W / (m×K).
[0145] Embodiment 2-4
[0146] Compared with Example 1, the difference is that the shear force F of the polyurethane structural adhesive at 50° C.-70° C. is different.
[0147] Example 5
[0148] Compared with Example 1, the difference is that epoxy resin structural adhesive is used, and the shear force F of the epoxy resin structural adhesive at 50° C.-70° C. is 0.6 MPa, and the thermal conductivity k is 0.4 W / (m×K).
[0149] Comparative Example 1
[0150] Compared with Example 1, the shear force F of the polyurethane structural adhesive used in Comparative Example 1 at 50° C.-70° C. is not within the range of 5 MPa-15 MPa, and the thermal conductivity k is not within the range of 0 W / (m×K)-0.8 W / (m×K).
[0151] Product parameters and performance parameters of Examples 1-5 and Comparative Example 1.
[0152] Table 1: Product parameters and performance parameters of Examples 1-5 and Comparative Example 1
[0153]
[0154] In Table 1, "F" indicates the shear force of the structural adhesive at 50°C-70°C; "Type of structural adhesive" indicates the type of structural adhesive used to bond the battery cell 10 and the box 3; "k" indicates the thermal conductivity of the structural adhesive; "Whether the vibration test fails" indicates whether the structural adhesive fails in the vibration test of the lithium-ion battery 10 at the corresponding temperature. For specific vibration test conditions and processes, please refer to the parameter test section below.
[0155] It should be understood that 40°C may represent the temperature at the geometric center of the largest surface of the battery cell 20 after charging at a charging rate of 3C or above starting from room temperature. 45°C may represent the temperature at the geometric center of the largest surface of the battery cell 20 after charging at a charging rate of 4C or above starting from room temperature.
[0156] According to the comparative analysis of the embodiments and the comparative examples, the structural adhesives in the embodiments 1-5 did not fail in the vibration test at 40°C; except for the embodiment 2, the structural adhesives in the other embodiments did not fail in the vibration test at 45°C, while the structural adhesive in the comparative example 1 failed in the vibration tests at both temperatures. This shows that the structural adhesive with a shear force of 5MPa to 15MPa and a thermal conductivity of 0W / (m×K) to 0.8W / (m×K) is not easy to fail in the fast-charged lithium-ion battery 10, and can provide good structural stability for the lithium-ion battery 10 at high temperatures, thereby improving the safety performance of the lithium-ion battery 10.
[0157] According to the comparative analysis of Examples 1-4, for lithium-ion batteries 10 with a charging rate of 4C or above, the temperature rise is higher, and a structural adhesive with a shear force in the range of 7MPa to 15MPa at 50°C to 70°C can be further selected. The thermal conductivity of the structural adhesive in this range is also lower.
[0158] Example 5 demonstrates that epoxy resin structural adhesive can also play a similar role as polyurethane structural adhesive under the condition of meeting the shear force range.
[0159] The following is a brief introduction to the test methods of the physical and chemical parameters and performance parameters involved in the embodiments of the present application. It should be understood that the following test methods are only examples, and other test methods known in the art may also be used for testing.
[0160] 1. Test method of shear force at high temperature
[0161] The shear test was carried out in a temperature chamber environment. Sample preparation and shear test were carried out with reference to GB / T 7124. The length of the bonding surface was controlled at 12.5±0.5mm; the thickness of the adhesive layer was designed to be 0.25±0.05mm.
[0162] 2. Charging time test method
[0163] Place the battery cell 10 to be tested on the charging pile, adjust the state of charge of the battery cell 10 to 10% SOC (the charge is 10% of the rated charge), and then charge it on the charging pile, and record the time it takes for the lithium-ion battery to be charged to 80% SOC (80% of the rated charge), that is, the charging time of the battery cell 10.
[0164] 3. Test method for electrolyte conductivity
[0165] The test method is in accordance with HG / T 4067-2015. The conductivity of the electrolyte to be tested is tested with a conductivity meter: about 100 ml of the sample to be tested is taken from a dry, clean, corrosion-resistant sample bottle, and sealed in a constant temperature water bath at 25±0.5℃. When the temperature of the sample to be tested is constant, the sample bottle cap is replaced with a rubber stopper with an electrode inserted. When the temperature is within the range of 25±0.5℃, the data is read, which is the conductivity of the sample to be tested.
[0166] 4. Test method for thermal conductivity of structural adhesive
[0167] According to ISO22007-2, a transient plane heat flow test is performed.
[0168] 5. Test method for mass fraction of inorganic filler
[0169] Use SEM or particle size analyzer to calibrate the particle morphology and mass fraction of the particles.
Claims
1. A lithium ion battery, characterized in that: The time t for charging the lithium-ion battery from 10% SOC to 80% SOC satisfies: t≤15min; The lithium-ion battery comprises: a box body and a battery cell disposed in the box body, wherein the battery cell is bonded to the box body by a structural adhesive; The shear force F of the structural adhesive at 50° C.-70° C. satisfies: 5Mpa≤F≤15Mpa.
2. The lithium-ion battery according to claim 1, characterized in that The battery cell includes an electrolyte, and the ion conductivity σ of the electrolyte satisfies: 9mS / cm≤σ≤25mS / cm.
3. The lithium ion battery according to claim 1 or 2, characterized in that: The structural adhesive includes at least one of polyurethane structural adhesive, acrylic structural adhesive, silicone and epoxy structural adhesive.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The thermal conductivity k of the structural adhesive satisfies: 0.05W / (m×K)≤k≤1.2W / (m×K).
5. The lithium-ion battery according to claim 4, characterized in that: 0.2W / (m×K)≤k≤0.8W / (m×K).
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The dynamic viscosity η of the structural adhesive satisfies: 200cps≤η≤100000cps.
7. The lithium ion battery according to any one of claims 3 to 6, characterized in that: The polyurethane structural adhesive includes an inorganic filler. Based on the total mass of the polyurethane structural adhesive, the mass fraction M1 of the inorganic filler satisfies: 5wt%≤M1≤80wt%.
8. The lithium-ion battery according to claim 7, characterized in that: 10wt%≤M1≤50wt%.
9. The lithium ion battery according to any one of claims 3 to 8, characterized in that: The raw materials for preparing the polyurethane structural adhesive include polyamide and polyol, and the volume ratio v1:v2 of the polyamide and the polyol satisfies: 4:1≤v1:v2≤1:
4.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The lithium-ion battery comprises a heat management component, which is attached to the surface of the battery cell with the largest area. The heat management component comprises a flow channel, which is used to contain a fluid to adjust the temperature of the battery cell.
11. The lithium ion battery according to any one of claims 1 to 10, characterized in that: The electrolyte includes a carboxylate solvent, and the carboxylate solvent includes at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate, and ethyl acrylate.
12. The lithium ion battery according to claim 11, characterized in that: Based on the total mass of the electrolyte, the mass fraction W1 of the carboxylic acid ester solvent satisfies: 5wt%≤W1≤80wt%.
13. The lithium ion battery according to claim 12, characterized in that: 10wt%≤W1≤40wt%.
14. The lithium ion battery according to any one of claims 1 to 13, characterized in that: The lithium-ion battery comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium-containing transition metal oxide, and the lithium transition metal oxide comprises Li 1+a [Ni x Co y Mn z M b ]O 2-c ; Wherein, M includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 0.7≥x≥0.65, 0.12≥y≥0.07, 0.3>z>0, 0.3>b≥0, 0.5≥c≥0.
15. The lithium ion battery according to any one of claims 1 to 14, characterized in that: The electrolyte includes a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
16. The lithium ion battery according to any one of claims 1 to 15, characterized in that: The electrolyte solution includes an electrolyte salt, and the electrolyte salt includes LiFSI.
17. An electrical device, characterized in that: The electrical device comprises the lithium-ion battery according to any one of claims 1 to 16.
Citation Information
Patent Citations
Flame-retardant high-temperature-resistant two-component polyurethane structural adhesive
CN115785879A
Drainage device of battery pack, battery pack and electric automobile
CN116487839A
Low-density polyurethane structural adhesive as well as preparation method and application thereof
CN117903741A
Electrolyte and lithium ion battery
CN118073654A
Battery cell, battery device, and electric device
CN119133576A